Optimal tuning of multi-machine power system stabilizers by the Queen-Bee Evolution technique. (March 2013) - Linda, M Mary; Nair, N Kesavan
A Queen-Bee Evolution-based tuning of a multi-machine power system stabilizer, which aims at enhancing the damping of the system over a wide range of operating conditions, is introduced in this paper. The basic components of this study are modeled by IEEE Model 1.1 and Heffron–Philips constants, considering the external resistance but neglecting the armature resistance. The problem is then formulated as a constrained multi-objective optimization problem. For investigation purposes, two different test systems are considered. The non-linear time domain simulations of the proposed power system stabilizer are compared with that based on the conventional approach power system stabilizer. The overall transfer function and the characteristic equation of the compensated system are derived from the single equivalent block diagram, and the nature of stability is verified by both frequency response analysis and Routh-Hurwitz (RH) criterion. Simulation results show that the proposed method motivates faster damping and leads to minimal overshoots in both speed and power angle deviations.